Arabic language book for the first intermediate grade A critical and linguistic study (Journal of the College of Basic Education, 2022)
The Arabic Language Book for the first intermediate grade is a pioneering experience in teaching the Arabic language in the schools of the country. It is an effective step in changing the stereotyping of the linguistic lesson in the secondary stage and an attempt to be made after it has been applied in most Arab countries. The first is the first experiment in Iraq, which is based on the complementary approach that followed the experiences of the brotherly Arab countries. " At the same time, it is a late step. It dates back to the 1990s, but only in the academic year (2016-2017) was it received by a selection of distinguished professors who were carefully chosen by the General Directorate of Curricula in the Ministry of Education. In this sense, the authors pointed out in the introduction to the book: "The student and the teacher will have a great role in this book and it is very clear without closing the eye. About Ah And therefore we are all confident that they remind us of weaknesses and strength in the article in order to strengthen the strengths and address the weaknesses do not recognize the work of the son of Adam from the shortage.